2010
DOI: 10.1007/s10750-010-0297-5
|View full text |Cite
|
Sign up to set email alerts
|

Resolving taxonomic uncertainties using molecular systematics: Salmo dentex and the Balkan trout community

Abstract: The genetic structure of Salmo dentex and its phylogenetic relations to sympatric salmonids in the Neretva and Skadar River basins were evaluated using mitochondrial DNA (mtDNA) control region, eight microsatellites, and somatolactin (SL) gene. In the Neretva River basin of Bosnia-Herzegovina, the results based on mtDNA analysis showed extensive haplotype sharing between S. marmoratus, S. dentex, and S. trutta, and were therefore not conclusive; however, F-statistics and assignment testing based on nuclear DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…The marbled pattern colouration seems not to be correlated with haplotypes of S. marmoratus . The sister species representative of the ‘marble trout lineage’ in Croatia and Montenegro is Salmo dentex (Snoj et al, ; Pustovrh et al, ). The partial marble pigmentation observed in Croatia and Montenegro is possibly the result of convergence, as happened in several populations of Salmo trutta from Norway with typical marble pigmentations (Delling, ).…”
Section: Resultsmentioning
confidence: 99%
“…The marbled pattern colouration seems not to be correlated with haplotypes of S. marmoratus . The sister species representative of the ‘marble trout lineage’ in Croatia and Montenegro is Salmo dentex (Snoj et al, ; Pustovrh et al, ). The partial marble pigmentation observed in Croatia and Montenegro is possibly the result of convergence, as happened in several populations of Salmo trutta from Norway with typical marble pigmentations (Delling, ).…”
Section: Resultsmentioning
confidence: 99%
“…: Previšić et al , 2009; aquatic leaf beetle Macroplea mutica : Mende et al , 2010) and terrestrial animals (brown bear Ursus arctos : Taberlet & Bouvet, 1994) have reported heterogeneous population structure within the Adriatic basin, and confirmed the arrangement of populations into distinct Balkan clades. Specifically, both Snoj et al (2010) and Pustovrh et al (2011) have also demonstrated the distinction between various trout populations [ S. trutta , Salmo dentex (Heckel 1851) and Salmo marmoratus Cuvier 1829] of River Neretva from those draining into Lake Skadar, which is especially noteworthy given the small geographic scale ( c . 150 km).…”
Section: Discussionmentioning
confidence: 98%
“…Such taxonomic changes have recently been shown for several fishes in the Aoos basin; for example, Markova et al (2010) insist that the Aoos is in fact inhabited by Barbus prespensis which also means that B. rebeli should be excluded from the Greek freshwater fish list, since this taxon is now considered endemic to a few river drainages in central western Albania. Furthermore, in the previous Greek checklists, S. dentex is noted as possibly inhabiting the Aoos (Kotellat & Freyhof, 2007;Economou et al 2007), yet this fish has been shown not to be a valid species (Snoj et al, 2010). Other serious taxonomic issues include the tiny sand gobies of Western Greece.…”
Section: Taxonomic Considerationsmentioning
confidence: 99%